Influence of ozonation and roasting on functional, microstructural, textural characteristics, and aflatoxin content of groundnut kernels. Issue 6 (7th September 2022) - Kaur, Gurjeet; Sidhu, Gagandeep Kaur; Kaur, Preetinder; Kaur, Amarjit
Abstract: The present study was conducted to evaluate the influence of ozonation, roasting and their combination on the moisture content, color, functional, structural, textural components, and aflatoxins in groundnut kernels. Samples were subjected to three treatments namely, dry roasting (R): 166°C for 7 min; gaseous ozone treatment (O): 6 mg/L for 30 min; combined ozonation‐roasting (OR): gaseous ozonation at 6 mg/L for 30 min followed by dry roasting at 166°C for 7 min. The ozonated‐roasted samples had the lowest moisture content (3.45%), the highest total phenolic content (4.18 mg gallic acid equivalents/100 g), and antioxidants capacity (69.59%). The treatments did not induce significant changes in color of kernels ( p < .05). Scanning electron microscopy indicated cracking of granules in roasted and swelling in ozonated kernels whereas more uniform orientation of granules was observed in ozonated‐roasted kernels. Roasted and ozonated kernels indicated a significant reduction of fracturability force to 54.60 and 14.11%, respectively, whereas ozonated‐roasted samples demonstrated a nonsignificant increase (4.37%). An increase in wave number of ozonated samples to 3, 289.37 cm −1 in Fourier transform infrared (FTIR) spectrum (FTIR) indicated stretching in OH groups. FTIR spectrum of ozonated‐roasted kernels suggested the formation of a new compound with CC and CC groups. The major aflatoxin B1 was reduced to maximum, that is, 100% in ozonated‐roasted kernels followed by ozonated (80.95%) and roasted (57.14%) samples. The findings indicate that the ozonation‐roasting treatment had a prominent role in the enhancement of functional compounds, structural and textural attributes along with the considerable reduction in aflatoxin content. Abstract : Ozonation‐roasting resulted in uniform and bigger granules as analyzed using scanning electron microscope; exhibited maximum fracturability. Using Fourier transform infrared, wave number corresponding to OH increased in ozonated, and a new compound with CC and CC groups was observed in ozonated‐roasted samples. Maximum reduction of aflatoxin B1, that is, 100% was found in ozonated‐roasted kernels followed by ozonated (80.95%) and roasted (57.14%) samples.